Inclusive radiative psi(2S) decays - Libby, J; Martin, L; Powell, A; Thomas, C; Wilkinson, G; Mendez, H; Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Hu, D; et al. (2009)
Using e+e- collision data taken with the CLEO-c detector at the Cornell Electron Storage Ring, we have investigated the direct photon spectrum in the decay ψ(2S)→γgg. We determine the ratio of the inclusive direct photon decay rate to that of the dominant three-gluon decay rate ψ(2S)→ggg (Rγ≡⌈Γgg(γgg)/⌈(ggg)) to be Rγ(zγ>0.4)=0.070±0.002±0.019±0.011, with zγ defined as the scaled photon energy relative to the beam energy. The errors shown are statistical, systematic, and that due to the uncertainty in the input branching fractions used to extract the ratio, respectively. © 2009 The American Physical Society.